On the occurrence of three blennid species in the South-eastern Mediterranean coast of Turkey - Erguden, Deniz; Sereflisan, Menderes; Uygur, Necdet (Acta Aquatica: Aquatic Sciences Journal, 2024)
In the present study, three blennid species of Aidablennius sphinx (Valenciennes, 1836) Parablennius tentacularis (Brünnich, 1768) and Scartella cristata (Linnaeus, 1758) were reported from the southeastern Mediterranean waters with visual records during an underwater survey conducted on October 19, 2015 in the Konacik and, on July 30, 2016 in the Ã‡evlik coast at a depth ranges of 2-10 m. The present report is the occurrence and is the first confirmation of three blennid species from Iskenderun Bay, Turkey (South-eastern Mediterranean Sea). Besides, this study will be useful fisheries biology and ecology and also contribute to fisheries scientists.Keywords: Blenniidae, Combtooth blennies; Iskenderun Bay; Mediterranean Sea; observation